Association of the polymorphism rs3918242 of the matrix metalloproteinase-9 gene with coronary artery disease in a younger population - Marjan Boshev; Stankovikj, Svetlana; Panov, Sasho; Josifovska, Slavica; Georgiev, Antonio; Poposka, Lidija; Pejkov, Hristo (Macedonian Academy of Sciences and Arts, 2023)
Coronary artery disease (CAD) is a complex disease resulting from the interaction of numerous so-called traditional risk factors and comorbid conditions on the one side (such as dyslipidemia, smoking, obesity, diabetes, hypertension) and genetic factors on the other. The evidence of a genetic contribution to the development of CAD, especially in the last 2 decades is consistent. It is important that a number of established gene polymorphisms in the younger CAD population are in the genes involved in the inflammatory response and tissue maintenance and remodeling processes. The aim of this study is to investigate the association of the rs3918242 polymorphism of the matrix metalloproteinase 9 (MMP9) gene with the coronary artery disease in the younger population. In this observational genetic-association study of cases and controls, the demographic, clinical, laboratory and genetic data of the younger population in a group of selected 70 CAD patients aged up to 45 years were analyzed, of which 35 patients have negative and 35 have positive coronary angiography finding, and 43 are men and 27 are women. The analysis of the genotypic and allelic frequency determined an association of the polymorphism and the occurrence of the positive coronary angiographic findings in the population of patients under the age of 45. The carriers of the heterozygous genotype CT have almost 5 times higher probability of having a positive coronary angiography finding compared to the carriers of the reference homozygous genotype CC (p=0.012). Thus, this parameter could be used for clinical risk assessment for the development of CAD.
Keywords: coronary artery disease; polymorphism(s); MMP9